DAMPAK KAPITASI KHUSUS TERHADAP CAPAIAN KINERJA FASILITAS KESEHATAN TINGKAT PERTAMA DI KABUPATEN - Muhammad Syukran; Firdaus Hafidz As Shidieq (Departemen Kebijakan dan Manajemen Kesehatan, Fakultas Kedokteran, Kesehatan Masyarakat, dan Keperawatan, Universitas Gadjah Mada, Yogyakarta Jl. Farmako Sekip Utara Yogyakarta 55281 Telp 0274-547490, 2020)
Background: Payment patterns at health facilities are an important component of the National Social Security System. Payment systemapplied by BPJS Kesehatan to primary health care is the capitation payment system and the establishment of special capitation paymentsfor primary health care in remote areas. The effort was made with the aim of improving the quality of service and primary healthcare performance. One of the districts receiving special capitation is Donggala, it is necessary to conduct research on the impact of thespecial capitation policy on the performance of primary health care in Donggala.Objective: This study aims to evaluate the impact of the special capitation policy on the performance of primary health care in Donggala.Methods: This study uses a quantitative observational study with a cross-sectional design. This study uses secondary data from theBPJS Kesehatan Palu branch and primary health care located in Donggala. Primary health care that are the subject of researchare 16 with a month as research unit for one year so that the total observations are 192 observations. Data analysis was carried outin stages, univariate, bivariate with chi square, and multivariate with logistic regression analysis.Results: Primary health care with special capitation have better performance outcomes compared to regular capitation in a certainperiod of time (OR = 3.67). Factors of human resource availability, namely general practitioners, dentists, and nurses will increase theprobability of achieving performance targets (OR = 5.32).Conclusion: The performance achievements of primary health care with special capitation is better than the regular capitation, the availabilityof human resources (i.e availability of general practitioners, dentists and nurses) have contributed to the performance improvementsof primary health care.